Fiqh Al-Bai's Review of Online Buying and Selling in Special Groups on Facebook Platform - Meirani, Nadia; Komalasari, Retno (Al-Muamalat: Jurnal Ekonomi Syariah, 2022)
Online buying and selling activities on the Facebook platform specifically for residents of Grand Cikarang City housing under the name of the Online Market group "Pasar Khusus COD Grand Cikarang City". With the development of online buying and selling, various kinds of risks arise that will haunt users, especially buyers, such as fraud, the obscurity of goods (gharar), incompatibility of goods and prices that reach the hands of the consumers, and so on. The purpose of this study is to find out the mechanism of buying and selling online in special groups on the Facebook platform and to find out the harmonization of Sharia Economic Law with buying and selling online in special market groups on the Facebook platform. The research method used in this research is a descriptive research method with qualitative data types. The results obtained in this study can be concluded that the implementation of online buying and selling in special groups on the Facebook platform uses a salam contract. There are cases where there is often uncertainty in terms of goods, prices, and the lack of certainty for the buyer to return the goods.